2015
DOI: 10.5539/jas.v7n11p254
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Bacteria and Fish Pathogenic Bacteria Found in Freshwater Aquaponic System

Abstract: Bacteria are very vital organisms in aquaponic system decomposing and converting the toxic components of the fish waste into usable vegetable nutrients; however, some unwanted bacteria could cause fish diseases. The purposes of this research were to compare the amount of bacteria in water from aquaponic catfish cultured in different stocking densities and Denaturing Gradient Gel Electrophoresis (DGGE) of Polymerase Chain Reaction (PCR)-amplified 16S rDNA was applied to characterise the bacterial populations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The genus Staphylococcus, also found in aquaponics by Chitmanat et al [37], consists of a number of species, of which S. aureus, S. epidermidis, and S. saprophyticus are the most frequently associated with human infection [58]. S. aureus is both a commensal bacterium and a human pathogen causing bacteremia and infective endocarditis as well as osteoarticular, skin and soft tissue, pleuropulmonary, and device-related infections [59].…”
Section: Bacteriamentioning
confidence: 98%
See 3 more Smart Citations
“…The genus Staphylococcus, also found in aquaponics by Chitmanat et al [37], consists of a number of species, of which S. aureus, S. epidermidis, and S. saprophyticus are the most frequently associated with human infection [58]. S. aureus is both a commensal bacterium and a human pathogen causing bacteremia and infective endocarditis as well as osteoarticular, skin and soft tissue, pleuropulmonary, and device-related infections [59].…”
Section: Bacteriamentioning
confidence: 98%
“…and Listeria monocytogenes in aquaponic water and the contaminated water did not lead to internalization of Shiga toxin-producing E. coli into the roots, leaves, and fruit of the lettuce, basil, and tomato plants studied. Also, while some authors reported the presence of E. coli and Salmonella in aquaponic systems [19,37], others did not find them [6,21]. Several investigations did not find one or more of the dangerous human pathogens E. coli O157:H7, Salmonella spp., and L. monocytogenes in aquaponic systems [6,22,38].…”
Section: Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…in the aquaponics lettuce samples (Elumalai et al 2017;Fox et al 2012;Moriarty et al 2018;Sirsat and Neal 2013). Chitmanat et al (2015) reported the presence of Aeromonas hydrophila, a bacterial fish pathogen and a suspected human pathogen causing diarrhoea (Daskalov 2006), in aquaponics systems containing catfish, but the authors did not investigate pathogen transmission or its effects on the crops. In addition, Schmautz et al (2017) reported a low occurrence of Aeromonas (0.25% of the total bacterial community) in the faecal samples of tilapia reared in an aquaponics system that included lettuce growing on a floating raft.…”
Section: Microbiological Safety Of Aquaponics Productsmentioning
confidence: 99%